Research progress in delineating the pathological mechanisms of GJB2-related hearing loss - Wang, Yujun; Jin, Yuan; Zhang, Qiong; Xiong, Ying; Gu, Xiang; Zeng, Shan; Chen, Wei (Frontiers in Cellular Neuroscience, 2023)
Hearing loss is the most common congenital sensory impairment. Mutations or deficiencies of the GJB2 gene are the most common genetic cause of congenital nonsyndromic deafness. Pathological changes such as decreased potential in the cochlea, active cochlear amplification disorders, cochlear developmental disorders and macrophage activation have been observed in various GJB2 transgenic mouse models. In the past, researchers generally believed that the pathological mechanisms underlying GJB2-related hearing loss comprised a K+ circulation defect and abnormal adenosine triphosphate-Ca2+ signals. However, recent studies have shown that K+ circulation is rarely associated with the pathological process of GJB2-related hearing loss, while cochlear developmental disorders and oxidative stress play an important, even critical, role in the occurrence of GJB2-related hearing loss. Nevertheless, this research has not been systematically summarized. In this review, we summarize the pathological mechanisms of GJB2-related hearing loss, including aspects of K+ circulation, organ of Corti developmental disorders, nutrition delivery, oxidative stress and adenosine triphosphate-Ca2+ signals. Clarifying the pathological mechanism of GJB2-related hearing loss can help develop new prevention and treatment strategies.